Space tourism : the elusive dream - Cohen, Erik; Spector, Sam (Tourism social science series, 2019)
This is the first comprehensive, multi-disciplinary work on the emergent phenomenon of space tourism. It is written by leading specialists and covers a wide spectrum of topics including space history and technology, the environmental, social, and legal aspects of the development of a future space tourism industry, and space tourism marketing.